Planes de manejo forestal y necesidades de informacion para el manejo operacional - Sabogal, C. (1998)
The main aim of this paper is to present some thoughts about natural forest management, management plans, information needs in management planning, and how to overcome some of the technical deficiencies existing. Emphasis is placed on management of hardwood neo-tropical natural forest exploitation and on information aspects as well as on the biophysical and silvicultural research needed for the planning, implementation and assessment of management techniques. There is a need to systematise and disseminate in a broader context the research findings and the practical experiences. Current biological, ecological and silvicultural knowledge relevant to management is not accessible enough for those involved in planning and/or in the forest management decision-making process.